Chew, shake, and tear: Prey processing in Australian sea lions (Neophoca cinerea) - Hocking, David P.; Ladds, Monique A.; Slip, David J.; Fitzgerald, Erich M. G.; Evans, Alistair R. (Marine mammal science, 2017)
Pinnipeds generally target relatively small prey that can be swallowed whole, yet often include larger prey in their diet. To eat large prey, they must first process it into pieces small enough to swallow. In this study we explored the range of prey‐processing behaviors used by Australian sea lions (Neophoca cinerea) when presented with large prey during captive feeding trials. The most common methods were chewing using the teeth, shaking prey at the surface, and tearing prey held between the teeth and forelimbs. Although pinnipeds do not masticate their food, we found that sea lions used chewing to create weak points in large prey to aid further processing and to prepare secured pieces of prey for swallowing. Shake feeding matches the processing behaviors observed in fur seals, but use of forelimbs for “hold and tear” feeding has not been previously reported for other otariids. When performing this processing method, prey was torn by being stretched between the teeth and forelimbs, where it was secured by being squeezed between the palms of their flippers. These results show that Australian sea lions use a broad repertoire of behaviors for prey processing, which matches the wide range of prey species in their diet.